Study of Building Energy Index and Energy Efficiency Measures for Residential Colleges at UTHM Main Campus - MOHD JAFFRI, NUR FATIHIN NAJILA BINTI; JAILANI, DR JUNAIDAH (Recent Trends in Civil Engineering and Built Environment, 2023)
Energy is one of the most important elements in the world. A case study was conducted to determine the energy and Building Energy Index (BEI) and energy efficiency measures in the building. The project is continued with the focus on the residential college at UTHM main campus which are Kolej Kediaman Tun Fatimah (KKTF) and Kolej Kediaman Tun Dr Ismail (KKTDI) where the project is performed by collecting energy usage and gross floor area for the residential colleges in the year 2019-2021. The calculation for building energy index (BEI) is calculated by using the formula energy usage per gross floor area. The comparison between the BEI calculation for residential colleges in UTHM main campus with the Malaysia Standard and the energy efficiency measures is proposed. It is expected to get a building energy index for the years 2019 to 2021 and the results were compared where the pattern was decreasing. It is estimated that the result was lower and satisfied the MS1525 Malaysia Standard, but the energy efficiency measures can be made for the residential colleges in UTHM main campus to improve the energy and electric usage.